Cruise transport service usage post COVID-19: The health belief model application. (September 2021) - Yuen, Kum Fai; Bin Saidi, Muhammad Syukri; Bai, Xiwen; Wang, Xueqin
Abstract: This study investigates the key psychological factors that influence customer's intention to use cruise services post COVID-19. A theoretical model grounded on consumer and health-driven theories (i.e. perceived value, perceived trust and health belief model) is developed. A survey questionnaire is designed and administered to 376 Chinese consumers. The theoretical model was tested via structural equation modelling. Results reveal that the constructs of the health belief model (i.e. perceived benefits, perceived health threat, self-efficacy and cues to action) have a significant effect on customers' perceived value towards cruise services. Perceived value then has direct and indirect effects on customers' cruise intention through perceived trust. This study enhances academic research by justifying customers' intention to use cruise services via consumer and health-belief viewpoints and provides implications for cruise management and policy formulation. Highlights: Analyse factors influencing cruise usage post COVID-19 Apply health belief, value and trust theories Perceived benefits, threat, self-efficacy and cues to action affect perceived value Value has direct and indirect effect on intention via trust Implicate policy formulation for cruise service management